The flat-footed fly genus Seri Kessel & Kessel (Diptera: Platypezidae) - Cumming, Jeffrey M.; Cumming, Heather J. (Zootaxa, 2011)
Systematic information on the rarely collected Holarctic platypezid genus Seri Kessel & Kessel is reviewed. Two species are included, S. obscuripennis (Oldenberg) from the Palaearctic Region and S. dymka (Kessel) from the Nearctic Region. The two species are diagnosed and the male of S. dymka is described for the first time. New records of S. dymka, previously recorded only from western North America, indicate that the species has a transcontinental distribution. The phylogenetic position and generic status of Seri is discussed.